Shifting the mean incident age for the five screenable cancers in Sulaymaniyah city-Iraq toward the younger age group, as a single-city experience for the last 12 years - Rashid Mahmud, Dara (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Recent trends have indicated a shift in the mean incident age for screenable cancers toward younger populations. This study examines this shift in Sulaymaniyah city, Iraq, over the last 12 years, in comparison to the data of developed and regional countries. Methods: A study was conducted on the data collected from health facilities in Sulaymaniyah. It focused on breast, colon, lung, prostate, and cervix cancers between the years 2011 and 2022. Results: The typical age at which these five malignancies were diagnosed decreased significantly in Sulaymaniyah. (P-value less than 0.001). The most noticeable changes were in prostate and colon/rectum cancers. Compared to nearby and advanced countries, Sulaymaniyah's average ages of occurrence were mostly lower. This indicates that there is a local trend or early detection methods in practice in this region. Conclusion: The study shows a big drop in average age of cancers found on screens in Sulaymaniyah. This implies that it is imperative to reevaluate cancer screening and prevention strategies, as the number young people falling ill has increased relative to previous years.